Поимот φρόνησις во контекст на Аристотеловата етика - Поповска, Јасмина (Здружение на класични филолози „Антика“, 2018)
The concept φρόνησις is not exclusively Aristotleʹs concept, but for the first time it occupies such an important place in one ethical theory. As argued in this article, its understanding is crucial for apprehending the key issues in Aristotleʹs ethics: the system of virtues, the doctrine of the mean, and the theory of εὐδαιμονία.The purpose of this text is to analyze the most important issues that this concept opens: its place in the system of virtues; its function in moral deliberation and setting of moral goals; its relationship with moral virtues and will; the possibility of constructing the “practical syllogism” through the question of obtaining the φρόνησις; and its relation with politics. Through the concept of φρόνησις the character of Aristotleʹs ethics can be shaped as an agent‐oriented, not action‐oriented ethics, ethics where the concern for developing the moral character, and not the consequence of actions is emphasized, and where the far‐reaching, and not the specific life goals are preferred.
Keywords: Aristotle, φρόνησις, ethics, practical syllogism